ACUTE COVID-19 IN THE THIRD TRIMESTER OF PREGNANCY - Людмила Станиславовна Ищенко; Екатерина Евгеньевна Воропаева; Элла Алексеевна Казачкова; Евгений Леонидович Казачков; Анна Юрьевна Холопова (Мать и дитя в Кузбассе)
To date, the impact of gestational age at the time of COVID-19 manifestation on pregnancy, labor, and birth outcomes remains controversial. The aim of the research – to assess the characteristics of the course and outcomes of pregnancy in women with manifestations of COVID-19 of varying severity in the third trimester of gestation. Materials and methods. The main study group included 751 pregnant women with manifestations of COVID-19 in the third trimester of gestation. Patients with a mild course of COVID-19 (n = 261) made up group 1, with a moderate course of infection (n = 385) – group 2, severe course (n = 94) – group 3, extremely severe course of infection (n = 11) – 4 group. 90 pregnant women in the third trimester with no history of COVID-19 – comparison group. Results. Mild (34.8%) and moderate (51.3%) course of COVID-19 predominates in the third trimester. COVID-19 in the third trimester is statistically significantly more often accompanied by placental insufficiency compared to pregnant women without COVID-19. Severe and extremely severe course of COVID-19 statistically significantly increases the incidence of preterm labor. With increasing severity of infection, anthropometric indices of newborns statistically significantly decrease, and the incidence of asphyxia increases. Extremely severe course of COVID-19 is associated with unfavorable maternal outcomes. During the period of recollection after COVID-19 in the third trimester, pregnancy, delivery, and neonatal status are not different compared with pregnant women without COVID-19. Conclusion. COVID-19 in the third trimester of gestation increases the likelihood of obstetric and perinatal complications. The course of pregnancy and birth outcomes for the mother and fetus during the period of convalescence of COVID-19 do not differ from those in uninfected women.